2022
DOI: 10.3390/biomedicines10040899
|View full text |Cite
|
Sign up to set email alerts
|

Potential Wound Healing Effect of Gel Based on Chicha Gum, Chitosan, and Mauritia flexuosa Oil

Abstract: Wounds are considered a clinically critical issue, and effective treatment will decrease complications, prevent chronic wound formation, and allow rapid healing. The development of products based on naturally occurring materials is an efficient approach to wound healing. Natural polysaccharides can mimic the extracellular matrix and promote cell growth, thus making them attractive for wound healing. In this context, the aim of this work was to produce a gel based on chicha gum, chitosan, and Mauritia flexuosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Besides, chondroitin sulfate could inhibit the activity of natural killer cells and elastase and improve the healing process [ 25 ]. Chitosan from natural sources contains intrinsic amine groups, and the aldehyde groups obtained by amidation can directly participate in the Schiff's base reaction, making it an ideal material for the preparation of dynamic hydrogels [ 26 ]. Collagen is the main component of the tendon-to-bone interface, providing essential structural stability [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, chondroitin sulfate could inhibit the activity of natural killer cells and elastase and improve the healing process [ 25 ]. Chitosan from natural sources contains intrinsic amine groups, and the aldehyde groups obtained by amidation can directly participate in the Schiff's base reaction, making it an ideal material for the preparation of dynamic hydrogels [ 26 ]. Collagen is the main component of the tendon-to-bone interface, providing essential structural stability [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are considered ideal matrices in the repair of articular cartilage due to the large amount of bound water [ 33 ]. Many studies have shown that hydrogels prepared using natural polymers act as an accelerating anti-inflammatory agent in wound healing [ 34 , 35 ]. Hydrogels are highly permeable to various drugs.…”
Section: Introductionmentioning
confidence: 99%